Nikolai Ivanovich Grodekov and his treatise «The Kyrgyz and Karakirgiz of the Syr-Darya region» - T. V. Kirpichenko; S. M. Naryzhnaya (Библиосфера)
The article considers the biography of N. I. Grodekov – the governor-general in Turkestan (1883–1893) and Amur region (1898–1902) in connection with the re-edition of his scientific ethnographic book «Kirghiz and karakirghiz of the Syr-Darya Region» in 2011.